Heat and electric flux coupling of closed-loop thermoelectric generator. (15th September 2021) - Wu, Zhanglin; Guo, Xuming; Xie, Guo; Yan, Tiantong; Wu, Dejian; Zhang, Fujie; Ang, Ran
Highlights: Heat and electric flux coupling of TEG was presented. Heat flow after closing circuit was amplified by 13% due to coupling. Reduction in maximum power output during the coupling was quantitatively elucidated. Double-edged sword of coupling for potential applications was discussed. Abstract: Thermoelectric generator (TEG) has been proved as a promising technology for directly converting heat into electricity based on Seebeck effect. On the contrary, this electricity can trigger a solid-state cooling based on conventional Peltier effect. However, these two effects induce a coupling between heat and electric flux, especially for the quantitative relationship still remaining a mystery. Here, we show experimental evidence and theoretical calculation for the coupling by monitoring transient response of fluid temperature and output power. The experimental maximum heat flow in open circuit is 1162 W at cold fluid flow rate V ̇ c = 0.3 m 3 /h and fluid temperature difference Δ T f = 70 °C, enhanced by 13% owing to heat compensation from intrinsic coupling in closed-loop circuit. Meanwhile, the measured maximum output power of TEG is 18.2 W, and subsequently decreases to 15.4 W due to the objective existence of coupling. This double-edged sword in coupling vigorously inspires the potential applications in heat-dissipation situation such as spacecraft, electronic components, photovoltaic, refrigerator and etc. Present findings open a novel avenue for manipulating heat-electricity conversion in practical engineering.